NILAI MORAL DALAM NOVEL MIMPI ANAK PULAU KARYA ABIDAH EL KHALIEQY - Siti Musyarofah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
This study was conducted with the aim to describe the moral values ​​contained in the novel Mimpi Anak Pulau written by Abidah El Khalieqy. The research approach used is a semiotic approach to the significance of the two-stage Barthes, namely denotative stage and connotative stage which is the unit of analysis in order to determine the meaning of moral values ​​in the novel Mimpi Anak Pulau written by Abidah El Khalieqyboth signs appear (manifest content) and the no visible or hidden (latent content). Data was collected by means of intensive reading, recording of data, collected and then analyzed and described in accordance with a focus on issues which are being analyzed based on the findings of the moral element analysis of novel Mimpi Anak Pulau written by Abidah El Khalieqy. Methods of data analysis in this research is done by intensive reading and study of novel based on the findings in the semiotic, heuristics, hermeneutics, and retroactively, and interpretation, which are next described and summarized. The results showed that there are some religious moral values ​​in the novel Children Dream Island Abidah El Khalieqi work.